Demonstrating the Utility of Egocentric Relational Event Modeling Using Focal Follow Data from Congolese BaYaka Children and Adolescents Engaging in Work and Play. Issue 3 (August 2021) - Ellis-Davies, Kate; Lew-Levy, Sheina; Fleming, Eleanor; Boyette, Adam H.; Baguley, Thom
Temporal aspects of child and adolescent time allocation in diverse cultural settings have been difficult to model using conventional statistical techniques. A new statistical approach, Egocentric Relational Event Modelling (EREM), allows for the simultaneous modelling of activity frequency, duration, and sequencing. Here, EREM is applied to a focal follow dataset of Congolese BaYaka forager child and adolescent play and work activities. Results show that, as children age, they engage in less frequent and extended play bouts and more frequent and extended work bouts. Bout frequency and duration were a more sensitive measure for early sex differences than overall time allocation. Sequential patterns of work and play suggest that these activities have short-term energetic trade-offs. This article demonstrates that EREM can reveal stable and variable patterns in child development.